1999
DOI: 10.1046/j.1475-1313.1999.00406.x
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal study of cycloplegic refraction in a cohort of 350 Japanese schoolchildren. Cycloplegic refraction

Abstract: We performed a 5 year longitudinal study of cycloplegic refraction in a cohort of 350 Japanese schoolchildren from 6 to 11 years of age in a rural area of southwestern Japan. The spherical refraction was measured under cycloplegia with an infrared autorefractometer. The grouped data from 350 right eyes showed leptokurtic frequency distributions, and the median was +0.91 D at age 6 yrs, shifted towards emmetropia with increasing age and reached +0.34 D at age 11 years. The prevalence of myopia of -1.0 D or more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
2

Year Published

2003
2003
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 12 publications
1
36
2
Order By: Relevance
“…They also reported that more boys than girls had myopia, although the difference was not significant. 3 The conflicting results in their study and ours probably reflect bias in our sampling selection, wherein younger children were more likely to participate in the trial than older children, and boys were more likely to participate in the trial than girls, when the degree of myopia is the same.…”
Section: Frequency Distribution Of Refractive Errorsmentioning
confidence: 57%
“…They also reported that more boys than girls had myopia, although the difference was not significant. 3 The conflicting results in their study and ours probably reflect bias in our sampling selection, wherein younger children were more likely to participate in the trial than older children, and boys were more likely to participate in the trial than girls, when the degree of myopia is the same.…”
Section: Frequency Distribution Of Refractive Errorsmentioning
confidence: 57%
“…, 2000), Chile (Maul et al. , 2000) and Japan (Watanabe et al. , 1999) have not found this gender difference.…”
Section: Discussionmentioning
confidence: 89%
“…If simple curvature is present, a second‐order (quadratic) polynomial is often an adequate fit to the data . For example, the two variables in Figure appear positively correlated and a straight line of positive slope to provide a good fit to the data.…”
Section: Resultsmentioning
confidence: 99%